The effect of grain size on workhardening and superplasticity in Zn/0.4% Al Alloy - Naziri, H.; Pearce, R. (College of Aeronautics, 1969)
Superplasticity*requires, amongst other things, a metal with a grain-size in the range 0.5-5μ. Theories of SP invoking dynamic recovery require that the cell-Size of the substructure for the alloy in question is larger than the SP grain-size, so that gliding dislocations are always annihilated in the grain boundaries and workhardening cannot occur (1,2). .Thus the grain-size is critical, and for a given set of conditions, there must be a grain-size greater than which SP cannot be achieved.